Respon Pertumbuhan dan Hasil Padi Gogo yang dipengaruhi oleh Pemberian Biochar dan Pupuk Hayati - Betty Natalie Fitriatin; Dzakaria Yogaswara; Tien Turmuktini; Emma Trinurani Sofyan; Anni Yuniarti (Soilrens, 2019)
One of the efforts to increase crop yield based in sustainable agriculture is through the utilization of microbial inoculants (biofertilizers) and soil conditioners. Biofertilizer is an ingredient that contains beneficial microbial inoculants to increase soil nutrient availability for plants. Biochar has been recognized as a soil conditioner by improving soil physical, chemical, and biological properties as well as in retaining nutrients, thereby enhancing plant growth. However, the research regarding the effect of the combination between biofertilizers and biochar on growth and yield of upland rice are still at scarce. The field experiment was conducted to determine the impact of biofertilizers and biochar on growth and yield of upland rice in Andisols at Pasir Talang village in Rancakalong district, Sumedang, West Java.  This experiment used a Randomized Block Design (RBD) consisted of six treatments and four replicates. Biofertilizers consisted of N-fixer bacteria (Azotobacter chroococum, Azospirillum sp.) and phosphate-solubilizer microbes (Pseudomonas mallei, P. cepaceae, Aspergillus niger and Penicillium sp.). The treatments were combination of biochar (2,4, and 6 t ha-1) and biofertlizers (0 and 50 kg ha-1). The result of experiment revealed that combination of biochar and biofertilizers increased the growth and yield of upland rice significantly. The application 4 t ha-1of biochar and 50 kg ha-1 of biofertilizers gave the best yield of 5,81 t ha-1.